Usefulness of oxidative stress biomarkers in native species for the biomonitoring of pesticide pollution in a shallow lake of the Austral Pampas, Argentina - Lombardero, Lucas Rodrigo; Pérez, Débora Jesabel; Medici, Sandra Karina; Mendieta, Julieta Renée; Iturburu, Fernando Gastón; Menone, Mirta Luján (Elsevier, 2024)
Pesticide contamination and its adverse effects on native freshwater species continue to be a worldwide major concern, mainly in developing countries. Passive biomonitoring of pesticide pollution in shallow lakes may be achieved by the simultaneous use of fish and wetland plants. Thus, the present study aimed to evaluate the occurrence of current-use pesticides in the surface water of a shallow lake of the Austral Pampas region (Buenos Aires Province, Argentina) surrounded by intensive agricultural activities and its relationship with a battery of biomarkers, including oxidative stress and genotoxicity, in two native species, the fish Oligosarcus jenynsii and the macrophyte Bidens laevis. A total of 26 pesticide residues were analyzed, and the main ones detected were glyphosate and its metabolite aminomethylphosphonic acid (AMPA), chlorpyrifos, and imidacloprid. In O. jenynsii, hydrogen peroxide (H2O2) content in the liver increased with chlorpyrifos occurrence, while malondialdehyde (MDA) levels in the brain and liver increased with the presence of both chlorpyrifos and glyphosate. In B. laevis, H2O2 and MDA levels in leaves and roots increased with AMPA occurrence. Also, leaf H2O2 contents and root MDA levels increased with chlorpyrifos concentration. In contrast, catalase and peroxidase activities in roots decreased with AMPA and chlorpyrifos occurrence. In both species, mainly H2O2 and MDA levels demonstrated their sensitivity to be used as biomarkers in the biomonitoring of current-use pesticide pollution in shallow lakes. Their use may provide information to plan strategies for environmental conservation by government institutions or decision-makers, and to assess the biota health status.